AWARENESS AND KNOWLEDGE OF EMERGENCY ROOM UTILIZATION AMONG THE SAUDI ARABIA POPULATION (CAHIERS MAGELLANES-NS, 2024)
Background: Emergency departments (EDs) are being used more frequently both in Saudi Arabia and worldwide in recent years which has been linked to the fact that about 50% of all ED cases are non-urgent patients. Objective: This study aimed to assess the awareness and knowledge surrounding emergency room utilization among the Saudi Arabian population, focusing on factors influencing ED use. Methods: A cross-sectional study was carried out by using an online administered questionnaire at one point of time. The target sampling was Saudi population. Data was collected and analyzed by using Statistical Package for the Social sciences (SPSS). Results: The study revealed that 89.3% of 702 participants recognized the ER as primarily for critical cases, with 71.2% indicating they would visit the ER when ill. Notably, 46.3% reported ER visits every 3 to 6 months, often citing limited primary care hours (34.0%) and resources (29.1%) as barriers. While 41.6% rated their ER experiences positively, 14.2% reported negative experiences. The leading reason for ER visits was fever without rash (50.1%), followed by chest pain and breathing difficulties. Overall, 57.0% exhibited low knowledge about ER use, whereas 27.2% and 15.8% had high and moderate knowledge levels, respectively. Knowledge levels correlated significantly with sociodemographic factors, including gender, age, nationality, marital status, employment, monthly income, education level, and region of residence. Conclusion: This study highlights a concerning gap in knowledge about appropriate ED use among the Saudi population, with implications for healthcare delivery and patient education. Enhanced awareness initiatives addressing the distinction between urgent and non-urgent medical needs are essential to optimize ED resources and improve overall healthcare outcomes in the region.